Contact Sensitivity of Turkish Children and Adolescents to European Baseline Series Allergens between 2013 and 2023 - Incilay Kalay Yildizhan; Ayse Boyvat (Mattioli1885, 2024)
Introduction: Raising the numbers of patch testing in suspected children increases the rate of diagnosis of allergic contact dermatitis and the identification of clinically relevant allergens. Objective: The aim of this study to identify the most frequently observed allergens among Turkish children and adolescents patch tested in 2013-2023. Methods: The patch test results of 160 patients (age ≤18) were analyzed retrospectively. The frequency of contact allergens and distribution of positive results in terms of gender, age group (children and adolescents), and the presence of atopic dermatitis (AD) were identified. Results: Forty-nine patients (30.6%), 34 girls and 15 boys, exhibited positive patch test reactions to a minimum of one allergen, and contact sensitivity was statistically significant higher in girls (P=0.034). The 5 most frequent allergens were nickel sulfate (10.6%), methylchloroisothiazolinone (MCI)/methylisothiazolinone (MI) (8.1%), cobalt chloride (5.6%), p-phenylenediamine (PPD) (5%), and MI (3.5%).  No significant association was observed between patch test positivity and age groups (p>.05). Nickel sulfate sensitivity was significantly higher in girls than boys (P=.043). A positive reaction was detected in 31.3% of patients with AD and in 33.7% of those without (P>.05) and a significant relationship was observed between contact sensitivity to fragrance allergens and AD (P=.046). Conclusion: Metals and preservatives represent the most frequent allergens in Turkish children and adolescents. Metal sensitivity is expected to decrease as legislation is enforced.  Regulatory measures are now required to reduce MI and MCI/MI contact allergy in Turkey.